(untitled) (World Economics and Finance Bulletin, 2025)
With a particular focus on Rafidain Bank in 2024, this study examines the critical role that organizational behavior (OB) plays in preserving service quality inside Iraqi banks. The study investigates how important OB elements—like cooperation, organizational culture, leadership styles, staff motivation, and communication effectiveness—relate to how well customers perceive the quality of the services they receive. The study intends to determine the precise OB behaviors that support or undermine service quality at Rafidain Bank using a mixed-methods methodology that includes surveys of bank staff and customers, maybe augmented by interviews and document analysis. The findings will provide valuable insights for bank management in Iraq, offering practical recommendations for improving OB practices to enhance service quality, customer satisfaction, and ultimately, the bank’s competitive advantage within the Iraqi banking sector. The study also seeks to contribute to the existing body of knowledge on the interplay between OB and service quality in developing economies, particularly within the context of the Iraqi banking industry.